2008
DOI: 10.1100/tsw.2008.49
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Lymphovascular Invasion in Clinically Localized Prostate Cancer after Radical Prostatectomy

Abstract: Whether lymphovascular invasion (LVI) is an independent prognostic factor in prostate cancer is still controversial. We retrospectively investigated its predictive role in disease progression following radical prostatectomy. The histological sections of radical prostatectomies from 71 clinically localized, prostatic adenocarcinoma patients were reviewed for LVI. Pre- and postoperative follow-up data were collected. LVI was identified in 15.5% of cases. Univariate analysis showed a significant association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
(21 reference statements)
2
23
0
1
Order By: Relevance
“…13 Baydar et al classified lymphovascular invasion as intratumoral (55%), at the periphery of the tumor (18%), both intra-and peritumoral (9%) and at a distant site from the tumor (18%). 11 The number of foci of lymphovascular invasion in each case has been shown to range from 1 to 40, with the majority of patients having 1 or 2 foci. 11,13,71 Lymphovascular invasion has been reported to be associated with adverse pathological features in radical prostatectomy specimens, 6 such as higher Gleason score, positive surgical margins, extraprostatic extension and seminal vesicle invasion, 12,16,18,[72][73][74][75] and with decreased time to biochemical progression, 13,16,18,19,72 distant metastases 8,19 and overall survival after radical prostatectomy.…”
Section: Lymphovascular Invasionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 Baydar et al classified lymphovascular invasion as intratumoral (55%), at the periphery of the tumor (18%), both intra-and peritumoral (9%) and at a distant site from the tumor (18%). 11 The number of foci of lymphovascular invasion in each case has been shown to range from 1 to 40, with the majority of patients having 1 or 2 foci. 11,13,71 Lymphovascular invasion has been reported to be associated with adverse pathological features in radical prostatectomy specimens, 6 such as higher Gleason score, positive surgical margins, extraprostatic extension and seminal vesicle invasion, 12,16,18,[72][73][74][75] and with decreased time to biochemical progression, 13,16,18,19,72 distant metastases 8,19 and overall survival after radical prostatectomy.…”
Section: Lymphovascular Invasionmentioning
confidence: 99%
“…11 The number of foci of lymphovascular invasion in each case has been shown to range from 1 to 40, with the majority of patients having 1 or 2 foci. 11,13,71 Lymphovascular invasion has been reported to be associated with adverse pathological features in radical prostatectomy specimens, 6 such as higher Gleason score, positive surgical margins, extraprostatic extension and seminal vesicle invasion, 12,16,18,[72][73][74][75] and with decreased time to biochemical progression, 13,16,18,19,72 distant metastases 8,19 and overall survival after radical prostatectomy. 18,19,67 Univariate analyses showed lymphovascular invasion to be a significant predictor of disease recurrence and/or progression following radical prostatectomy, 12,15,17,[72][73][74][75] and multivariate analyses have confirmed that lymphovascular invasion is an independent predictor of disease recurrence, when controlling for other pathological variables known to influence clinical outcome.…”
Section: Lymphovascular Invasionmentioning
confidence: 99%
See 2 more Smart Citations
“…LVI has been associated with decreased time to biochemical progression, distant metastases, and overall survival after RP. In addition, LVI has been shown to act as an independent predictor of disease recurrence when controlling for other pathologic variables known to influence clinical outcome [24]. Figure 1c is the map distribution of the tumour whose pathology report is summarised in Table 1.…”
Section: Histopathologic Typementioning
confidence: 99%